ADSORPTION AND KINETICS OF METHYLENE BLUE ON MODIFIED LAPONITE - Kalbaev, Alisher; Mamataliyev, Nozim; Abdikamalova, Aziza; Ochilov, Akbarjon; Masharipova, Mavjuda (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This investigation presents the findings on the adsorption and kinetics of methylene blue using a modified laponite-based adsorbent. The research demonstrated that methylene blue could be effectively adsorbed from aqueous solutions. The adsorption processes were analyzed based on Langmuir and Freundlich isotherm models, with the pseudo-second-order kinetic model showing the best fit to the data. Due to its high surface area and efficient ion-exchange capacity, the modified laponite can serve as an alternative adsorbent in water purification processes. The results highlight the potential of laponite for environmentally safe removal of dyes from industrial wastewater.